A descriptive evaluative study of the suitability of the existing built in storage units in a selected female dormitory in the University of the Philippines Diliman in relation to anthropometric standards of height and reach - Guerra, Claire Ann A.; Reodique Catherine C. (2011.)
This study evaluated the suitability of the existing built-in storage in a selected female dormitory to its users based from Panero and Zelnik's anthropometric standards of height and reach (1979). The respondents were selected through convenience sampling and were composed of 85 female college students with ages ranging from 17 to 23 years old. The dimensions of the existing built-in storage units were evaluated against the respondents' height and reach measurement based from Panero and Zelnik (1979) and comfortable reach based from Diffrient and Tilley (1981). Percentile selection was used to determine the wider range of users to be accomodated. An inventory of hung and folded clothing articles and other items stored in the closet was conducted to determine the storage space requirements of the respondents. It was found that the dimensions of the existing built-in storage units do not fit the required comfortable height and reach measurements and the storage space requirements of the respondents. This study suggests the importance of application of anthropometrically oriented references and standards in order to optimize the fitting of designed product to its users, as a user-centered design approach wherein the design process is upon hard data concerning the physical characteristics of the users.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Built-in furniture; Dormitories -- Philippines